2005
DOI: 10.2136/vzj2004.0184
|View full text |Cite
|
Sign up to set email alerts
|

Bias in Ponded Infiltration Estimates Due to Sample Volume and Shape

Abstract: with estimates increasing as much as a factor of 20 when the scale of measurement increased from 0.1 to 2 m (e.g., Estimates of saturated and unsaturated water flow in soil are impor- Garbesi et al., 1996;Tidwell and Wilson, 1999). tant for predictions of infiltration, runoff, and solute transport. Previ-Measurement bias related to sample size has someous research indicates that ponded infiltration estimates are influenced by the volume or cross-sectional area of the measurement. Our study times been attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
2
24
1
Order By: Relevance
“…Further, measurements of steady infiltration rate were made after each measurement period in dividing the cumulative infiltration water depth for the period by the required times (Wuest, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Further, measurements of steady infiltration rate were made after each measurement period in dividing the cumulative infiltration water depth for the period by the required times (Wuest, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement error due to lateral flow decreased as the outer ring size increased, and consequently the measured infiltration rates better approximated the one-dimensional vertical flow rates. More recently, Wuest (2005) investigated the influence of sample volume and shape on estimates of saturated flow in a cylinder infiltrometer and demonstrated that the mean infiltration rate increased as the diameter increased, while the standard deviation and range also increased with increasing diameter. Then Wuest (2005) concluded that these phenomena might be attributed to deep insertion of the cylinder and high antecedent soil moisture.…”
Section: Buffer Index Effects On Hydraulic Conductivity Measurements mentioning
confidence: 99%
“…The hardpan classification is the result of a discontinuous silica layer developed between 1.0 to 1.5 m (3.3 to 4.9 ft) below the soil surface, less than 10 mm (0.4 in) thick and occupying less than 15% of the area. This feature does not adversely affect soil surface hydrologic properties; Wuest (2005) conducted four-hour ponded infiltration tests within 500 m (1,640 ft) of the plots reported on here. The infiltration rates did not change after four hours, indicating that deep, less pervious layers were not influential.…”
Section: Methodsmentioning
confidence: 99%
“…The inside circumference was tamped with a 4 mm (0.2 in) thick rod to seal any gaps between the cylinder and the soil. Water was maintained at a constant depth of 20 to 30 mm (0.8 to 1.2 in) with float valves for two hours (Wuest 2005). Two hours were sufficient to achieve near steady-state infiltration, which was usually approached within 30 to 60 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation